Evaluation of Websites for Development of Listening Skills - Málek, Jan (Univerzita Pardubice, 2017)
This bachelor paper deals with the use of internet websites to develop listening skills of English language learners. The theoretical part focuses on communicative competence. Next, it presents the concept of listening as a skill and lists various types of listening. The third chapter of the theoretical part deals with the use of computers and the Internet as modern didactic means. The last chapter of the theoretical part examines the learner in the context of curricular documents. The practical part of the thesis establishes a checklist of criteria for evaluating websites that are designed to develop listening skills in English. Subsequently, these criteria are used to evaluate such websites.
Hodnocení internetových stránek pro rozvoj poslechu
Keywords: poslech; internetové stránky; hodnocení; rast; listening; websites; evaluation; checklist